2010
DOI: 10.2298/sarh1010577s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of metabolism modifiers of cyclic nucleotides on contractility of right ventricle of rat heart with intact and removed endocardial endothelium

Abstract: An intact endocardial endothelium is necessary for completion of contractile performance of the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The endocardium is a natural biological barrier between the circulating blood of the ventricles and cardiomyocytes, including endocardial and microvascular endothelial cells. The endocardium is essential for cardiac embryonic development, cardiac contraction, rhythm, and remodeling ( Brutsaert, 2003 ; Smiljić et al, 2010 ). Endocardial injury reduces endothelial-mediated NO release and cardiomyocyte sensitivity to Ca 2+ and contractility ( Shen et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The endocardium is a natural biological barrier between the circulating blood of the ventricles and cardiomyocytes, including endocardial and microvascular endothelial cells. The endocardium is essential for cardiac embryonic development, cardiac contraction, rhythm, and remodeling ( Brutsaert, 2003 ; Smiljić et al, 2010 ). Endocardial injury reduces endothelial-mediated NO release and cardiomyocyte sensitivity to Ca 2+ and contractility ( Shen et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that myocardial contractility depends on the presence of EE and the degree of its damage regardless of the technique employed to remove the endothelium: immersion in 1% Triton X-100, mechanical peeling, exposure to a high-frequency ultrasound, or flow rate of dry air. Fully removing or partially damaging EE cells directly affect contractile cardiac performance causing a lower contractility of cardiomyocytes [4,5]. The inotropic effect of EE is achieved through the synthesis and release of endothelial mediators, the sensory ability to detect changes in blood plasma and the quality of bloodheart barrier to control transendothelial transport.…”
Section: Introductionmentioning
confidence: 99%